2009
DOI: 10.1029/2008jc004976
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of the Equatorial Undercurrent at 10°W as inferred from recent in situ observations

Abstract: [1] Eighteen cross-equatorial shipboard current profiling sections along 10°W with conductivity-temperature-depth measurements taken between 1997 and 2007 are used to analyze the mean meridional structure and the seasonal variability of the Equatorial Undercurrent (EUC) at 10°W. Our analysis suggests a seasonal cycle for the EUC transport at 10°W, with a well-defined annual harmonic and some indication of a semiannual component, with a first maximum in January and a second stronger maximum from June to Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 38 publications
6
51
0
Order By: Relevance
“…Consistent with the findings of Oudot and Morin (1987), uplift of the pycnocline, which supplies the EUC with nutrients, plays an important role in the enrichment process within the equatorial band. The seasonal differences in various parameters revealed in our study are in agreement with previous findings regarding seasonal variability in the Gulf of Guinea, where the seasonal equatorial upwelling and thermocline lifting are more enhanced in June than in September (Voituriez and Herbland, 1979;Oudot and Morin, 1987;Kolodziejczyk et al, 2009). Also, in agreement with Jouanno et al (2011), it is shown here that the intensification of the northern branch of the SEC around 1°N in June 2005 enhanced the vertical shear just above the core of the EUC, causing vertical mixing and equatorial cooling to be stronger in June than in September.…”
Section: Seasonal Upwelling Influencesupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with the findings of Oudot and Morin (1987), uplift of the pycnocline, which supplies the EUC with nutrients, plays an important role in the enrichment process within the equatorial band. The seasonal differences in various parameters revealed in our study are in agreement with previous findings regarding seasonal variability in the Gulf of Guinea, where the seasonal equatorial upwelling and thermocline lifting are more enhanced in June than in September (Voituriez and Herbland, 1979;Oudot and Morin, 1987;Kolodziejczyk et al, 2009). Also, in agreement with Jouanno et al (2011), it is shown here that the intensification of the northern branch of the SEC around 1°N in June 2005 enhanced the vertical shear just above the core of the EUC, causing vertical mixing and equatorial cooling to be stronger in June than in September.…”
Section: Seasonal Upwelling Influencesupporting
confidence: 82%
“…The general track of the six EGEE cruises conducted between 2005 and 2007 is presented in Figure 1 (Kolodziejczyk et al, 2009(Kolodziejczyk et al, , 2014Nubi et al, 2014 for additional details). Seawater samples were collected in 11 or 22 (depending on the cruise/research vessel used) hydrological bottles attached to a rosette, together with a CTD-O2 (bathysonde) and ship-mounted acoustic Doppler current profiler (SADCP).…”
Section: Sampling and Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to this programme, the oceanic mixed layer and upwelling processes are better known Caniaux et al, 2010;Wade et al, 2010), as well as the oceanic circulation there (Kolodziejczyk et al, 2009). However, the marine atmospheric boundary layer (MABL) processes remain poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…Given the small amount of data in the region, it is not possible to precisely validate these values, however their orders of magnitude are reasonably consistent with existing climatologies [Key et al, 2004;Kolodziejczyk et al, 2009;Garcia et al, 2014].…”
mentioning
confidence: 71%